Ad Avoidance in Hair Care Market: Reiteration of Need for Consumer Justice - Anand, Sandip (Indian Journal of Marketing, 2008)
A very high degree of TV ad avoidance is a fact established by various studies. There are various reasons observed for this behaviour worldwide. There have been attempts to understand the relationship of ad avoidance with the product used. However, there is lack of holistic understanding of ad avoidance in the specific context of a product. In the given context, this study was done to understand the reasons for ad avoidance in the context of hair care category. It has been found that consumers are neither receiving 'information value' nor 'entertainment value' from TV. advertisements. Though there is relationship between brand used and ad recall but the viewers are not very satisfied with the ads, which they watch. It necessitates the incorporation of this consumer demand into the ad creation and delivery. The incorporation of consumer's voice is likely to create efficiency of information exchange and likely to provide consumer justice for the consumers. This is also likely to create a meta organization, where consumers become integral part of the organization and influence the process of ad creation and delivery.